2006
DOI: 10.1111/j.1600-0420.2006.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of diabetic macular oedema following high altitude exercise

Abstract: Hyperopic patients with a previous history of malignant glaucoma can be made aware of an imminent attack by observing when their VA improves without the aid of corrective spectacles. Surgeons need to be aware that biometric measurements and IOL calculations in these abnormal eyes may be inaccurate, particularly if the measurements are made when the patient is in absolute or relative aqueous misdirection. This case illustrates that extremely large refractive shifts () 8.0 D) in association with aqueous misdirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Resolution of macula oedema and reduced retinal thickness has been reported in a diabetic patient during HBO therapy. 35 No changes in intraocular pressure or axial length of the eye occurred in these patients after treatment, which is in line with results reported in other studies using the similar HBO treatment protocol. 4,5,12 A limitation of the study is that posterior surface of the lens appeared visible only in one third of the patients because of restricted dilation of the pupil.…”
Section: Discussionsupporting
confidence: 91%
“…Resolution of macula oedema and reduced retinal thickness has been reported in a diabetic patient during HBO therapy. 35 No changes in intraocular pressure or axial length of the eye occurred in these patients after treatment, which is in line with results reported in other studies using the similar HBO treatment protocol. 4,5,12 A limitation of the study is that posterior surface of the lens appeared visible only in one third of the patients because of restricted dilation of the pupil.…”
Section: Discussionsupporting
confidence: 91%
“…Another way to reduce the hydrostatic pressure in the microcirculation is to constrict the arterioles. This may be done simply by breathing oxygen-enriched air which has been shown to constrict retinal blood vessels and reduce diabetic macular edema (111)(112)(113)(114). Retinal oxygenation may also be improved by scattered laser treatment, which destroys a part of the retina and thereby reduces its oxygen consumption (17,22,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50).…”
Section: How Do We Treat Edema?mentioning
confidence: 97%
“…Although some studies have suggested the beneficial effects of living at HA on glucose homeostasis, the relationship between HA and DR remains unclear owing to multiple factors and potential confounders, such as varying altitudes of the investigated population, duration of exposure to HA, genetic backgrounds, living conditions, dietary habits, and physiological adaptation. Table 1 summarizes the main findings of previous studies [9][10][11][12][13][14][15] that explored the impact of HA on DR. This review aimed to comprehensively explore the impact of HA exposure on DR, encompassing genetic adaptations, changes in glucose homeostasis, and related factors.…”
Section: Introductionmentioning
confidence: 99%